2012
DOI: 10.1039/c2nr30349c
|View full text |Cite
|
Sign up to set email alerts
|

A facile method to prepare SnO2 nanotubes for use in efficient SnO2–TiO2 core–shell dye-sensitized solar cells

Abstract: A high-efficiency photoelectrode for dye-sensitized solar cells (DSSCs) should combine the advantageous features of fast electron transport, slow interfacial electron recombination and large specific surface area. However, these three requirements usually cannot be achieved simultaneously in the present state-of-the-art research. Here we report a simple procedure to combine the three conflicting requirements by using porous SnO(2) nanotube-TiO(2) (SnO(2) NT-TiO(2)) core-shell structured photoanodes for DSSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
110
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 31 publications
(36 reference statements)
5
110
0
1
Order By: Relevance
“…Due to synergistic effects, some hybrid systems containing two different metal oxides exhibit better electrochemical performance than single systems [15][16][17][18][19][20]. Therefore, in this paper, the electrospinning technique was applied to fabricate SnO 2 -C fibers containing NiO (SnO 2 -NiO-C fibers) with enhanced battery performance.…”
Section: Introductionmentioning
confidence: 98%
“…Due to synergistic effects, some hybrid systems containing two different metal oxides exhibit better electrochemical performance than single systems [15][16][17][18][19][20]. Therefore, in this paper, the electrospinning technique was applied to fabricate SnO 2 -C fibers containing NiO (SnO 2 -NiO-C fibers) with enhanced battery performance.…”
Section: Introductionmentioning
confidence: 98%
“…Order of magnitude higher l n is reported in SnO 2 nanowires and flowers than NPs [11]. Many wet-chemical methods are reported for synthesis of various morphologies of SnO 2 as WE in DSSCs; [12][13][14][15] but produced inferior efficiency (g). For instance, Wang et al [16] synthesized hollow nanospheres (HNS) and reported g < 1% in pristine SnO 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Hence, hierarchical nanostructured SnO 2 is indispensable for achieving high-performanced photoanode. On the other hand, to combine the advantageous features of SnO 2 and TiO 2 , various SnO 2 /TiO 2 composite nanomaterials also have been synthesized and exhibit interesting photovoltaic performance in DSSCs application [27][28][29].…”
Section: Introductionmentioning
confidence: 99%